2014
DOI: 10.1177/1532440013520245
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the Effects of Redistricting on Electoral Competition, 1972–2012

Abstract: In this note, we revisit the work of Carson and Crespinto examine the effect of different redistricting plans on competitiveness in U.S. House elections. Similar to the previous results, our probit estimates on an expanded dataset that includes redistricting cycles from 1972 to 2012 reveal that commission and court-drawn districts experience more competition on average than those drawn by legislatures. These results provide additional support for the hypothesis that one way to increase the competitiveness of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…To my knowledge, no scholar has examined whether the margin of victory in congressional elections is associated with judicial redistricting over so long a time period, nor has any scholar theorized that judicial partisan calculation of the sort I describe—in which judges deliberately target districts held by contrapartisans for increased electoral competition—leads to systematically different outcomes in legislative elections. I find that judicial redistricting plans have resulted in more competitive elections than plans drawn by state legislatures and non‐independent commissions (consistent with Cottrill and Peretti and Carson, Crespin, and Williamson ). Further, I find that since judges may rightly be seen as actors in or attendant to a political regime and as doing the bidding of their preferred partisan coalitions, judges drawing districts appear to advance the electoral interests of their copartisan candidates for Congress (consistent with the extant literature on judicial partisanship and election litigation [e.g., Lloyd ; Kopko ; Peretti ]).…”
supporting
confidence: 70%
See 2 more Smart Citations
“…To my knowledge, no scholar has examined whether the margin of victory in congressional elections is associated with judicial redistricting over so long a time period, nor has any scholar theorized that judicial partisan calculation of the sort I describe—in which judges deliberately target districts held by contrapartisans for increased electoral competition—leads to systematically different outcomes in legislative elections. I find that judicial redistricting plans have resulted in more competitive elections than plans drawn by state legislatures and non‐independent commissions (consistent with Cottrill and Peretti and Carson, Crespin, and Williamson ). Further, I find that since judges may rightly be seen as actors in or attendant to a political regime and as doing the bidding of their preferred partisan coalitions, judges drawing districts appear to advance the electoral interests of their copartisan candidates for Congress (consistent with the extant literature on judicial partisanship and election litigation [e.g., Lloyd ; Kopko ; Peretti ]).…”
supporting
confidence: 70%
“…Studies have also suggested that independent commissions and courts should consider nonpartisan considerations that are intended to enhance electoral competition such as district compactness, responsiveness, and accountability (Butler and Cain 1992;Hirsch 2003). Other research has shown that districts shaped by commissions and courts (i.e., through nonlegislative redistricting) experience more competitive elections than those that undergo redistricting conducted by partisan state legislatures (Carson and Crespin 2004;Grose 2011;Cottrill 2012;Cottrill and Peretti 2013;Lindgren and Southwell 2013;Carson, Crespin, and Williamson 2014). No empirical relationship has been demonstrated between the partisanship of judges and electoral rewards for those judges' copartisans in congressional elections (at least from 2002 to 2010) (Cottrill and Peretti 2013), but some isolated , 1982-2012. nonpartisan plans commissioned by judges have seemed to reflect demonstrable copartisan bias (Kousser 1996).…”
Section: Judges and Legislators: Divergent Incentives For Electormentioning
confidence: 99%
See 1 more Smart Citation
“…My goal in the paper is to measure the effect of redistricting commissions on electoral competition in the US House of Representatives. Prior work in this area (McDonald, 2006;Lublin & McDonald, 2006;Yoshinka & Murphy, 2011;Winburn, 2011;Masket, Winburn, & Wright, 2012;Carson, Crespin, & Williamson, 2014) has produced conflicting results, with some studies finding pro-competitive effects and others finding little if any effect.…”
Section: Introductionmentioning
confidence: 99%
“…This measure of electoral competition has two important advantages over more commonly-used measures. First, the district normalized presidential vote (DNPV) is continuous, unlike the binary dependent variable employed in many other studies of electoral competition, including Carson, Crespin and Williamson (2014), the work to which this paper is most closely linked. When a binary dependent variable is employed, districts are deemed either competitive or safe depending on whether the winner's share of the major party vote in a district falls above or below some arbitrary cutoff point.…”
Section: Introductionmentioning
confidence: 99%